2023
DOI: 10.1021/acs.joc.3c00052
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Homo-Nazarov-Type Cyclization of Benzonorcaradienes: Stereoselective Synthesis of Hydrochrysenes

Abstract: Formal homo-Nazarov cyclization of benzonorcaradienes produced by intramolecular hydroarylation of arylated alkynylcyclopropanes promoted by TfOH has been described, providing stereoselective access to highly substituted hydrochrysenes. An unprecedented 1,2-acyl migration occurred for the 2-heteroaroyl substrates, thus giving the same products as their 3heteroaroyl analogs. Moreover, these products could be readily oxidized by air to fully π-conjugated chrysenes after decarboxylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Among the various rearrangement reactions of DACs, the Cloke–Wilson rearrangements of cyclopropyl ketone to dihydrofuran, cyclopropyl imine to pyrroline, cyclopropyl ester to γ-butyrolactone, cyclopropyl amide to γ-butyrolactam, and other rearrangements such as nitrocyclopropane to isooxazoline- N -oxide involve the formation of new C–O or C–N bonds in the products (1,3-migration of carbon atom). Similarly, the vinylcyclopropane to cyclopentene rearrangement, homo-Nazarov rearrangement of cyclopropyl vinyl/aryl ketones to cyclohexenones/α-tetralones, and other rearrangements involve the formation of a new C–C bond (1,3- or 1,4-migration). However, a rearrangement involving the breaking and reformation of C–C bond between vicinal ring carbons (1,2-migration) has been seldom observed in DAC chemistry. , Few years back, we reported that aroyl-substituted DACs 1 upon treatment with AlCl 3 undergo ring-opening, fragmentation (cleavage of C–C bond), and 1,2-aroyl migration to vicinal carbon (reformation of C–C bond) to give γ-ketoesters 2 (which undergo further cyclization to yield 2-pyrones under the reaction conditions) (Scheme , eq 1) .…”
mentioning
confidence: 99%
“…Among the various rearrangement reactions of DACs, the Cloke–Wilson rearrangements of cyclopropyl ketone to dihydrofuran, cyclopropyl imine to pyrroline, cyclopropyl ester to γ-butyrolactone, cyclopropyl amide to γ-butyrolactam, and other rearrangements such as nitrocyclopropane to isooxazoline- N -oxide involve the formation of new C–O or C–N bonds in the products (1,3-migration of carbon atom). Similarly, the vinylcyclopropane to cyclopentene rearrangement, homo-Nazarov rearrangement of cyclopropyl vinyl/aryl ketones to cyclohexenones/α-tetralones, and other rearrangements involve the formation of a new C–C bond (1,3- or 1,4-migration). However, a rearrangement involving the breaking and reformation of C–C bond between vicinal ring carbons (1,2-migration) has been seldom observed in DAC chemistry. , Few years back, we reported that aroyl-substituted DACs 1 upon treatment with AlCl 3 undergo ring-opening, fragmentation (cleavage of C–C bond), and 1,2-aroyl migration to vicinal carbon (reformation of C–C bond) to give γ-ketoesters 2 (which undergo further cyclization to yield 2-pyrones under the reaction conditions) (Scheme , eq 1) .…”
mentioning
confidence: 99%